SOCIOCYBERPHYSICAL SYSTEMS’ SECURITY MODELS - Milevsky, Stanislav (Ukrainian Information Security Research Journal, 2023)
The object of the study is the process of building multi-contour systems for the protection infrastructure elements of socio-cyber-physical systems based on a modification of the Lotka-Volterra model. The article presents the formation of security models for socio-cyber-physical systems based on the Lotka-Volterra model, which allows determining preventive measures of the security system against targeted (mixed) attacks with integration with social engineering methods and the possibility of hybridity and synergism signs. This approach allows, based on the initial data on the socio-political (economic) component, to determine the possibility of influencing the general opinion of both a separate society and certain age groups. In addition, the identification of signs of hybridity and synergism of cyber threats in the main components of socio-cyber-physical systems: social networks, the cloud and the physical component allows to determine the basic principles of building multi-contour security systems, considering the external and internal security contour systems on each platform. For the formation of multi-contour information protection systems of socio-cyber-physical systems, possible scenarios of the implementation of targeted attacks and their directionality are considered. And also, the possibility of influencing the socio-psychological state through social networks of formal and informal "leaders" of society.